New media producing new labor: Pinterest, yearning, and self-surveillance. Issue 4 (7th August 2016) - Jones, Hillary A.
ABSTRACT: Scrapbooks, a medium long used by women to curate experiences, employ a past-oriented affective capacity of remembrance. By engaging in modal analysis, this essay explores how the social networking site Pinterest, although visually similar to scrapbooks, instead offers a future-oriented affective capacity of yearning to its (primarily female) users. This temporal pivot and change in affective capacity engages women not in celebratory memory work but in a postindustrial, postfeminist third shift of labor curating yearning and self-surveilling.